Ultrasensitive Ambient Mass Spectrometric Analysis with a Pin-to-Capillary Flowing Atmospheric-Pressure Afterglow Source - Shelley, Jacob T. (2011)
The advent of ambient desorption/ionization mass spectrometry has resulted in a strong interest in ionization sources that are capable of direct analyte sampling and ionization. One source that has enjoyed increasing interest is the Flowing Atmospheric-Pressure Afterglow (FAPA). FAPA has been proven capable of directly desorbing/ionizing samples in any phase (solid, liquid, or gas) and with impressive limits of detection (<100 fmol). The FAPA was also shown to be less affected by competitive-ionization matrix effects than other plasma-based sources. However, the original FAPA design exhibited substantial background levels, cluttered background spectra in the negative-ion mode, and significant oxidation of aromatic analytes, which ultimately compromised analyte identification and quantification. In the present study, a change in the FAPA configuration from a pin-to-plate to a pin-to-capillary geometry was found to vastly improve performance. Background signals in positive- and negative-ionization modes were reduced by 89% and 99%, respectively. Additionally, the capillary anode strongly reduced the amount of atomic oxygen that could cause oxidation of analytes. Temperatures of the gas stream that interacts with the sample, which heavily influences desorption capabilities, were compared between the two sources by means of IR thermography. The performance of the new FAPA configuration is evaluated through the determination of a variety of compounds in positive- and negative-ion mode, including agrochemicals and explosives. A detection limit of 4 amol was found for the direct determination of the agrochemical ametryn, and appears to be spectrometer-limited. The ability to quickly screen for analytes in bulk liquid samples with the pin-to-capillary FAPA is also shown.